Perception and practices with regard to tooth shade selection for composite restoration among dentists in Southwest, Nigeria - Lillian Lami Enone; Afolabi Oyapero; John O Makanjuola (Wolters Kluwer Medknow Publications, 2020)
Background: The perception of tooth color is an important goal for the dentist who needs to choose the right tooth shade to create satisfactory esthetic restorations as well as for the patient who desires a better smile. The success of any tooth-colored (anterior) restoration is however directly related to the accuracy of chairside shade selection The aim of this study was to determine the knowledge and practices of dentists on shade selection in composite restorations in Southwest, Nigeria. Materials and Methods: This descriptive self-administered questionnaire-based study was conducted among 200 randomly enlisted dentists selected by multistage sampling in the Southwest of Nigeria. Chi-square statistical test was utilized for categorical variables, while the independent t-test was used to compare the mean values in subgroups. A multivariate linear regression model was used to assess the association between predictor variables and knowledge scores. The level of significance in this study was set at 0.05. Results: Majority of respondents had good knowledge (67.5%), while 60.5% of them had good practices. The highest proportion (66.5%) used only visual shade selection in natural daylight (89.0%), while only 48% determine the tooth shade at the cervical, middle, and incisal third of the tooth; 73% had never taken a color blind test. Dentists had practiced for more than 10 years and restorative dentistry consultants had significantly better knowledge about shade selection. Respondents who had poor knowledge had significantly poorer shade selection practices (P = 0.036). After controlling for confounders by multivariate logistic regression, all categories of dentists with good knowledge and consultants still had significantly better dental shade selection practices. Conclusion: Experienced dentists and restorative consultants appear to have adequate knowledge about shade selection and this had a significant impact on their practice. A need however exists to bridge the gap among other categories of dental personnel to improve the esthetic outcome of composite restorations.